PENGARUH LEVERAGE DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN JASA SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PADATAHUN 2012-2016 - Rizki Zulfikar; Narisa Putri Hanendya (Jurnal Ilmu Keuangan dan Perbankan (JIKA), 2016)
ABSTRACKDividend payout ratio is influenced by several factors including the debt to total asset ratio and net profit margin. Phenomenon occurring in property and real estate companies is in a period of an decrease in dividend payout ratio when the companies obtained a decrease in debt to total asset ratio and increase in net profit margin.The method is used in this research is descriptive method, verification with quantitative approach. The analytical method used is multiple regression. Besides previously also classical assumption which include normality test, test Multicollinearity, Heteroskidastity test and autocorrelation test. pearson correlation analysis,determination coefficient, and hypotesis test. The results showed that there were no irregularities classical assumptions, it is shown that the available data has been qualified to use multiple linear regression models. The method of analysis used is multiple linear regression analysis with the help of analysis tools SPSS version 16.0The research shows that partially, debt to total asset ratio is no not significantly influencing dividend payout ratio and net profit margin is significantly influencing dividend payout ratio. Simultaneously, debt to total asset ratio and net profit margin is significantly influencing dividend payout ratio.Keyword :debt to total asset ratio, net profit margin, and dividend payout ratio